Brain Text and Traumatic Postmemory in Jonathan Safran Foer's Extremely Loud and Incredibly Close - Gao, Ercong (Archīum Ateneo, 2024)
By adopting Nie Zhenzhao’s conception of brain text, this paper explicates the generation of traumatic postmemories as represented in Extremely Loud and Incredibly Close by Jonathan Safran Foer, a third-generation descendant of Holocaust witnesses. The authors argue that the traumatic effects of great catastrophic events, such as the Holocaust during the Second World War and the 9/11 terrorist attacks in 2001, can be transformed into brain texts of horror and trauma of the survivors, which, with time passing by, become the traumatic postmemories of the survivors’ descendants who have not experienced these events. As far as this novel is concerned, by applying language texts, simulated images, and the Jewish consciousness characteristic of Jewish literature, Foer attempts to reveal the generative process of brain texts and postmemories of the survivors’ descendants about the two catastrophic events, and also that of the novelist himself, which serves as a catalyst for his writing of postmemory fiction. In this sense, Foer’s literary text helps to construct contemporary people’s postmemories, demonstrating the complexity and continuity of the trauma suffered by the descendants of the victims of World War II and terrorist attacks.